Sarbanes-Oxley guide for finance and information technology professionals - Anand, Sanjay (John Wiley & Sons, 2006)
Praise for Sarbanes-Oxley Guide for Finance and Information Technology Professionals"Effective SOX programs enlist the entire organization to build and monitor a compliant control environment. However, even the best SOX programs are inefficient at best, ineffective at worst, if there is a lack of informed, competent finance and IT personnel to support the effort. - Resumé vydavatel
Keywords: účetnictví -- Spojené státy americké; zákony -- Spojené státy americké; obchodní společnosti -- Spojené státy americké; účetní výkazy -- Spojené státy americké; zpřístupňování informací -- Spojené státy americké; accounting -- United States; laws -- United States; corporations -- United States; financial statements -- United States; accessibility of information -- United States; příručky; elektronické knihy; handbooks and manuals; electronic books